Effect of Antenatal Mental Health Disorder on Fetal Growth: A Systematic Review - Handayani, Rina Tri; Widiyanto, Aris; Atmojo, Joko Tri; Setyorini, Catur (Journal of Maternal and Child Health, 2020)
Background: Maternal mental disorders during pregnancy are associated with a range of adverse health outcomes for infants. Re